Current Status of Familial Hypercholesterolemia in China: A Need for Patient FH Registry Systems - Chen, Peipei; Chen, Xi; Zhang, Shuyang (Frontiers in Physiology, 2019)
Background: Familial hypercholesterolemia (FH) greatly facilitates the development of cardiovascular disease (CVD). Without timely treatment, the incidence of coronary heart disease (CHD) in patients with FH is 3 to 4 times that in non-FH patients, and the onset of CVD would be advanced by approximately 10 years. There is ample evidence that the diagnosis and adequate treatment of FH are not properly considered for all ethnicities. The monogenic cause of FH includes apolipoprotein B (APOB), low-density lipoprotein receptor (LDLR), and proprotein convertase subtilisin/kexin 9 (PCSK9). There are approximately 2,765,420 to 6,913,550 cases of potential heterozygous FH (HeFH) and 2,205 to 4,609 cases of potential homozygous FH (HoFH) in China. Nevertheless, China lacks clinical diagnostic criteria specific to Chinese patients, such that most FH patients cannot be diagnosed until middle age or after their first cardiovascular event, thus precluding early treatment. Objective: This article explores the gene mutations, diagnosis and treatment of FH patients in China. Following the implementation of the two-child policy, there is a need to establish Chinese FH registry systems and genetic databases and to address the challenges in conducting cascade screening and long-term management. Conclusion: Advocating the establishment of FH registry systems and databases is an important rate-limiting step in improving long-term prognosis in FH patients, so that joint efforts of clinical experts and public communities are required. We recommend a process flow from case identification to entry into the registry system, and the widespread use of the system in clinical applications can provide the best treatment guidance for medical practice.